ผลของโปรแกรมพัฒนาลักษณะมุ่งอนาคตที่มีต่อความสามารถในการเผชิญและฟันฝ่าอุปสรรคของนักเรียนประถมศึกษาปีที่ 5 - วรัฐา นพพรเจริญกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The purpose of this research was to study effects of future orientation program on adversity quotient of fifth graded students. Subjects consisted of 60 students semester 2 and academic year 2018 from Office of the Private Education Commission school. Instruments used in this study included a future orientation program and an adversity quotient test. Data collection consisted of 3 phases: pretest, posttest and delayed posttest. Data was analyzed employing independent t-test and One-way Repeated Measures (ANOVA). Findings were as follows: 1) After receiving the future orientation program, experimental group students had posttest scores and delayed-posttest scores of the adversity quotient test significantly higher than their pretest scores at the .05 level of significance. 2) Experimental group students had posttest and delayed-posttest scores of adversity quotient test significantly higher than those of the control group at the .05 level of significance.